1997
DOI: 10.1515/cclm.1997.35.1.29
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and Tamoxifen Prevent the Over-Glycosylation of Rat Trabecular Bone Collagen Induced by Ovariectomy

Abstract: Summary:We have recently demonstrated that ovariectomy in the rat causes over-glycosylation of collagen which is restricted to trabecular bone. In order to obtain further evidence, we studied whether estrogen or tamoxifen treatment prevented over-glycosylation of trabecular bone collagen. Forty one-hundred-day-old female rats were subjected to ovariectomy (n = 30) or sham-operation (n = 10). Starting the day of the operation, sham-operated rats were treated with vehicle, while ovariectomized rats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It has been reported that collagen glycosylation may contribute to structural and biological functions, such as control of collagen fibrillogenesis [84-87], collagen cross-linking [37,88,89] and collagen-cell interaction [90,91]. It has been reported that altered collagen glycosylation is associated with bone disorders, such as osteogenesis imperfecta [92-94], postmenopausal osteoporosis [95,96] and osteosarcoma, osteofibrous dysplasia [97], suggesting the significant roles of collagen glycosylation in mineralization. The most predominant glycosylated site of type I collagen, α1/2 Hyl-87, is one of the major helical cross-linking sites [98,99].…”
Section: Type I Collagenmentioning
confidence: 99%
“…It has been reported that collagen glycosylation may contribute to structural and biological functions, such as control of collagen fibrillogenesis [84-87], collagen cross-linking [37,88,89] and collagen-cell interaction [90,91]. It has been reported that altered collagen glycosylation is associated with bone disorders, such as osteogenesis imperfecta [92-94], postmenopausal osteoporosis [95,96] and osteosarcoma, osteofibrous dysplasia [97], suggesting the significant roles of collagen glycosylation in mineralization. The most predominant glycosylated site of type I collagen, α1/2 Hyl-87, is one of the major helical cross-linking sites [98,99].…”
Section: Type I Collagenmentioning
confidence: 99%
“…In bone, type I collagen is relatively less glycosylated (15,26,27); however, in bone/skeletal disorders, such as osteogenesis imperfecta (20, 28 -30), postmenopausal osteoporosis (19,23,31,32), osteosarcoma, osteofibrous dysplasia (21), and Kashin-Beck disease (33), altered collagen glycosylation occurs, and this has been implicated in mineralization defects. Due to the structure of the carbohydrates and the glycosylation sites, structural as well as biological functions have been proposed for collagen glycosylation (i.e.…”
mentioning
confidence: 99%
“…It has been reported that altered collagen glycosylation is associated with bone disorders (35)(36)(37)(38)(39)(40)(41)(42). However, the role of LH3 in type I collagen modification and bone biology has not been investigated.…”
mentioning
confidence: 99%